2018
DOI: 10.1103/physrevlett.120.106801
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Quasiparticle Scattering Signals in Bilayer Graphene Due to Layer Polarization and Destructive Interference

Abstract: We study chemically gated bilayer graphene using scanning tunneling microscopy and spectroscopy complemented by tight-binding calculations. Gating is achieved by intercalating Cs between bilayer graphene and Ir(111), thereby shifting the conduction band minima below the chemical potential. Scattering between electronic states (both intraband and interband) is detected via quasiparticle interference. However, not all expected processes are visible in our experiment. We uncover two general effects causing this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Figure 1c depicts an ARPES scan of bilayer graphene/Ir(111) which shows two π bands (labels π 1 and π 2 ) instead of one π band which is observed for monolayer graphene/Ir(111). The two observed parabolic π valence bands are consistent with Bernal (or AB) stacking 40 and in agreement with earlier reports on bilayer graphene on Ir(111) 14 . An equi-energy cut around the K point at a binding energy E B = 0.7 eV is shown in Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Figure 1c depicts an ARPES scan of bilayer graphene/Ir(111) which shows two π bands (labels π 1 and π 2 ) instead of one π band which is observed for monolayer graphene/Ir(111). The two observed parabolic π valence bands are consistent with Bernal (or AB) stacking 40 and in agreement with earlier reports on bilayer graphene on Ir(111) 14 . An equi-energy cut around the K point at a binding energy E B = 0.7 eV is shown in Fig.…”
Section: Resultssupporting
confidence: 92%
“…1a, b is significantly reduced by Cs intercalation. This is evident from previous works which measured Fourier transform scanning tunneling spectroscopy on Cs-intercalated bilayer graphene 14 . We believe that the flat substrate obtained by Cs intercalation is also important for the subsequent growth of Cs films.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…1b. 1,2,[19][20][21][22][23]4,5,11,[14][15][16][17][18] One angle-resolved photoemission study reported an orientation corresponding to Fig. 1c, 24 although the experimental resolution did not allow unambiguous determination of the low energy TW orientation.…”
Section: Main Textmentioning
confidence: 99%